Analysis of Innovative Practices in Human Resource Activity - Пейчева, Мирослава (Научни трудове, 2024)
The study’s aim is to analyze innovation practices in human resources activities. The main tasks are: to analyze the theory of innovative HR practices; to collect information about innovative HR practices in world-famous organizations; to draw basic conclusions. The object of the research is HR functions. The subject is the impact of innovations on human resources activity and the competencies of the specialists in this field. The research toolkit covers analysis and synthesis. Some of the main conclusions are: there are new models of work in HR activity; there are new HR duties; a new way of training HR specialists is needed. The results can be used in the development of a new syllabus.